Establishment of the Thai-China-ASEAN Research Institute of Krirk University According to the Guidelines of the Belt and Road Initiative Project - Yong, Luo; Phuttha, Somchai (Arts of Management Journal, 2024)
This academic article aims to determine the guidelines of the research institute of Krirk University according to the Belt and Road Initiative (BRI) Project. Regarding BRI, it is a project in which more than 152 countries in almost every region participated and devoted resources to achieve the same goal. The BRI network, both land and sea, is a gathering of 10 ASEAN member countries. Such an approach will be derived from future research. The authors have formulated a framework for the study based on the conceptual factors of organization and modern organizational management and the Belt and Road Strategy, which has a process of managing the concept of learning organizations in the digital era, the knowledge management community of practice (CoP), collaboration networks, and principles of research institute management. The research results will be presented to the president of Kriek University for the policy application of how-to management of the "Thai-China-ASEAN Research Institute" to study the context of the project and follow up on the impact on people in the target areas. There are management guidelines for the institution’s management; enhancing collaboration with relevant organizations and organizing a Community of Practice (CoP) can be proposed. From the process and content, the implementation will lead the institute to be an academic support for Thailand, China, and ASEAN countries. The study results will be used to develop educational administrative policies according to social and economic development principles and the United Nations’ sustainable development goals (SDGs); therefore, civil societies and various groups of people can use them to build cooperation in further development.